Law the Development of the 1982 UN Convention on the Law of the Sea: An Australian Perspective - Letts, David (UI Scholars Hub, 2020)
Attempts to achieve a comprehensive codification of the law of the sea were eventually successful with the entry into force of the 1982 UN Convention on the Law of the Sea. Australia played a key role in the negotiations that led to the finalization of the 1982 Convention and this involvement has shaped the manner in which Australia has subsequently dealt with law of the sea issues. This paper reviews aspects of Australian practice as the 1982 Convention was being negotiated and then considers Australian state practice by examining three case studies that have particular significance for Australia and Indonesia: the Indonesian archipelagic sea lanes designation; the MV Tampa incident and the maritime boundary conciliation between Australia and Timor Leste. The paper concludes with some observations regarding how Australia’s approach to the law of the sea has evolved.